From Neurodevelopmental to Neurodegenerative Disorders: The Vascular Continuum - Ouellette, Julie; Lacoste, Baptiste (Frontiers in Aging Neuroscience, 2021)
Structural and functional integrity of the cerebral vasculature ensures proper brain development and function, as well as healthy aging. The inability of the brain to store energy makes it exceptionally dependent on an adequate supply of oxygen and nutrients from the blood stream for matching colossal demands of neural and glial cells. Key vascular features including a dense vasculature, a tightly controlled environment, and the regulation of cerebral blood flow (CBF) all take part in brain health throughout life. As such, healthy brain development and aging are both ensured by the anatomical and functional interaction between the vascular and nervous systems that are established during brain development and maintained throughout the lifespan. During critical periods of brain development, vascular networks remodel until they can actively respond to increases in neural activity through neurovascular coupling, which makes the brain particularly vulnerable to neurovascular alterations. The brain vasculature has been strongly associated with the onset and/or progression of conditions associated with aging, and more recently with neurodevelopmental disorders. Our understanding of cerebrovascular contributions to neurological disorders is rapidly evolving, and increasing evidence shows that deficits in angiogenesis, CBF and the blood-brain barrier (BBB) are causally linked to cognitive impairment. Moreover, it is of utmost curiosity that although neurodevelopmental and neurodegenerative disorders express different clinical features at different stages of life, they share similar vascular abnormalities. In this review, we present an overview of vascular dysfunctions associated with neurodevelopmental (autism spectrum disorders, schizophrenia, Down Syndrome) and neurodegenerative (multiple sclerosis, Huntington’s, Parkinson’s, and Alzheimer’s diseases) disorders, with a focus on impairments in angiogenesis, CBF and the BBB. Finally, we discuss the impact of early vascular impairments on the expression of neurodegenerative diseases.